DESIGN AND INVITRO CHARACTERIZATION OF METFORMIN LOADED RESEALED ERYTHROCYTES - S, Aiswarya; S, Parvathy; Tp, Aneesh; Viswanad, Vidya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Metformin is an oral antidiabetic drug in the biguanide class. It is the first-line drug of choice for the treatment of type 2 diabetes. The objective of this study was to retard the release of metformin using carrier erythrocyte for getting a parenteral slow release depot formulation. Methods: The study retards the release of metformin by encapsulating in carrier erythrocyte. Endocytosis is the method used for the encapsulation of the drug metformin. Results: The optimized formulation shows 98.34% of drug release within 12 days. From the in vitro release data, zero order kinetic graph shows the best fit graph. % cell recovered was found to be 73-78% and it suggests that the loading technique was less destructive. Conclusion: The optimized formulation is a perfect carrier for the parenteral slow release depot of metformin. Keywords: Resealed erythrocytes, Cross-linking, Cell recovery, Endocytosis, Slow release depot formulation.